Protective Role of Black Tea Extract against Nonalcoholic Steatohepatitis-Induced Skeletal Dysfunction - Subhra Karmakar; Sangita Majumdar; Anasuya Maiti; Monalisa Choudhury; Aniruddha Ghosh; Asankur S. Das; Chandan Mitra (Journal of Osteoporosis)
Aim. This paper aimed to examine the chemoprotective actions of aqueous black tea extract (BTE) against nonalcoholic steatohepatitis- (NASH-) induced skeletal changes in rats. Material. Wistar rats (body wt. 155–175 g) of both sexes, aged 4–5 months, were randomly assigned to 3 groups; Group A (control), Group B (60% high-fat diet; HFD), and Group C (HFD + 2.5% BTE). Methods. Several urinary (calcium, phosphate, creatinine, and calcium-to-creatinine ratio) serum (alkaline phosphatase and serum tartrate-resistant acid phosphatase), and molecular markers of bone turnover (receptor activator of NF-κB ligand (RANKL), osteoprotegerin (OPG), and estrogen) were tested. Also, several bone parameters (bone density, bone tensile strength, bone mineral content, and bone histology) and calcium homeostasis were checked. Results. Results indicated that HFD-induced alterations in urinary, serum, and bone parameters as well as calcium homeostasis, all could be significantly ameliorated by BTE supplementation. Conclusion. Results suggest a potential role of BTE as a protective agent against NASH-induced changes in bone metabolism in rats.